Climate-induced limnological change in shallow lakes during the Little Ice Age - Seitz, Carina (2020)
One of the challenges in recent years is understanding how shallow lakes will respond to global warming, particularly in arid and semiarid regions. Since variations in precipitation can produce significant ecological changes due to changes in water level (WL) and chemical and physical water characteristics of the lake, understanding the effect of changes in climate in the past can help better to address the impact of climate warming in shallow lakes. Thus, we selected four Pampean shallow lakes (Puan, Los Chilenos, Sauce Grande, and La Salada) strategically located in a climatically sensitive transition zone from arid to semiarid to assess the main drivers and mechanisms of long-term ecological change. These lakes originated in the Late Holocene as temporary and clear water lakes, and then around ~910 to 480 cal. yr BP they changed permanent with turbid waters, except by Puan that changed at ~20 cal. yr BP (1930 AD). The primary mechanism of change was an increase in WL and the resuspension of the sediment by increase precipitation and wind intensity. All the lakes presented a rise in WL during the climate period associated with the Little Ice Age (LIA), except Puan, which had dry conditions during the LIA and WL increase when humid conditions returned. The LIA was not homogeneous in the Pampean Region. It was dry in Puan and the eastern and northern Pampas and wet in La Salada, Sauce Grande, Los Chilenos, and the southern and western Pampas. Human-induced eutrophication was produced only in recent times.